2001
DOI: 10.1016/s0045-6535(00)00081-3
|View full text |Cite
|
Sign up to set email alerts
|

Removal of estrogenic activities of bisphenol A and nonylphenol by oxidative enzymes from lignin-degrading basidiomycetes

Abstract: Bisphenol A (BPA) and nonylphenol (NP) were treated with manganese peroxidase (MnP) and laccase prepared from the culture of lignin-degrading fungi. Laccase in the presence of 1-hydroxybenzotriazole (HBT), the so-called laccase-mediator system, was also applied to remove the estrogenic activity. Both chemicals disappeared in the reaction mixture within a 1-h treatment with MnP but the estrogenic activities of BPA and NP still remained 40% and 60% in the reaction mixtures after a 1-h and a 3-h treatment, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
138
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 214 publications
(145 citation statements)
references
References 28 publications
5
138
0
2
Order By: Relevance
“…7), indicating oxidative coupling of primary oxidation metabolites. Similarly, the formation of polymerization products was reported for nonylphenol and bisphenol A degradation by laccases and manganese peroxidases from white-rot fungi (Tsutsumi et al, 2001;Uchida et al, 2001), which led to the removal of the oestrogenic activities of the contaminants (Tsutsumi et al, 2001). In aquatic ecosystems, laccase-catalysed degradation of endocrine disruptors may lead to their removal from these environments by formation of bound residues with organic matter, as already proposed for oxidoreductasecatalysed degradation of chlorophenols in presence of stream fulvic acids (Sarkar et al, 1988).…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…7), indicating oxidative coupling of primary oxidation metabolites. Similarly, the formation of polymerization products was reported for nonylphenol and bisphenol A degradation by laccases and manganese peroxidases from white-rot fungi (Tsutsumi et al, 2001;Uchida et al, 2001), which led to the removal of the oestrogenic activities of the contaminants (Tsutsumi et al, 2001). In aquatic ecosystems, laccase-catalysed degradation of endocrine disruptors may lead to their removal from these environments by formation of bound residues with organic matter, as already proposed for oxidoreductasecatalysed degradation of chlorophenols in presence of stream fulvic acids (Sarkar et al, 1988).…”
Section: Discussionsupporting
confidence: 58%
“…The oxidation of nonylphenol and bisphenol A, another phenolic environmental pollutant with endocrine activity, by laccases from white-rot basidiomycetes (Fukuda et al, 2001;Tsutsumi et al, 2001;Uchida et al, 2001) and soil-derived ascomycetes (Saito et al, 2003) has previously been demonstrated. Both pollutants are also degraded by the extracellular ligninmodifying enzyme manganese peroxidase (EC 1.11.1.13) produced by white-rot fungi (Tsutsumi et al, 2001).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…In recent years, several research groups have explored the ability of free fungal laccases to remove a wide range of hormones: genistein, estrone, 17b-estradiol, estriol, and 17a-ethinylestradiol (Auriol et al 2008;Nicotra et al 2004;Tamagawa et al 2006;Lloret et al 2010). Crude and purified laccase from Trametes versicolor and Trametes villosa were used to degrade bisphenol A (Kim and Nicell 2006) and nonylphenol (Tsutsumi et al 2001).…”
Section: Introductionmentioning
confidence: 99%